Implications of Reading Interest in Improving Language Intelligence in Early Children - Pujiati, Isti (International Proceedings of Nusantara Raya, 2023)
Language intelligence can be seen when various stimulations and efforts can be provided by the environment around the child. Language intelligence is a skill that can be used and competently structured through words to convey ideas in speaking, reading and writing. There are many activities that can be pursued in improving language intelligence in early childhood. Early childhood is the most important period in honing all skills including language skills. There are previous researchers who examined the effectiveness of reading interest which influences language development with various background efforts. The researcher was then interested in reviewing several articles from the researchers so that the formulations and results that had been tested could be taken. The research was conducted using a qualitative descriptive method by analyzing data, namely in the form of previous research article documents that had been carried out on the theme of reading interest and its relation to language intelligence in early childhood. The techniques chosen are content analysis techniques, note-taking techniques, and listening techniques. From the research conducted, it was found that through reading interest built by the child's environment, namely the family environment, school environment, and community environment continuously and sustainably, an increase in children's language development is obtained and children have language intelligence when the three environments synergize strongly and compact.